Polarization in Media Discourses on Europeanization in Spain - Ana Pérez-Escoda; Sonia Boulos; Maria-José Establés; Lucía García-Carretero (Politics and Governance, 2023)
Political and media polarization has had a detrimental impact on democratic principles and democratic processes on a global scale. In Europe, such polarization has eroded the trust in national and European institutions and has challenged the basic values that stand at the heart of the European integration project. The aim of this study is to analyze Spanish media discourses on Europeanization, with an attempt to identify key areas in which polarizing narratives related to Europeanization are more prevalent. To conduct our study, six national media outlets were selected based on four criteria: media format, ownership, ideology, and consumption. A final sample of 540 news items collected between July 2021 to March 2022 was selected for analysis. Using a qualitative methodological approach, the study was carried out in two stages. In the first phase, we conducted a content analysis to identify the main topics discussed in relation to the European Union and the actors represented in them. This led to the identification of polarizing narratives and discourses emerging in the context of the discussed topics. In the second phase, we used critical discourse analysis to analyze polarizing discourses.